Mediterranean diet in the management and prevention of obesity - Ligia J. Dominguez; Nicola Veronese; Giovanna Di Bella; Claudia Cusumano; Angela Parisi; Federica Tagliaferri; Stefano Ciriminna; Mario Barbagallo (Experimental Gerontology, 2023)
The current pandemic of obesity represents a major global public health problem, mainly due to its association with chronic non-communicable disabling conditions and with increased mortality. Population aging increases the chances of non-communicable chronic diseases allowing a longer exposure to risk factors for these disabling conditions. Obesity is a major risk factor contributing to pathological aging. Numerous epidemiological studies have shown that the risk of death due to cardiovascular disease and cancer increases progressively as overweight and obesity rise. Nutrition research is now focused on the effects of combinations of foods in dietary patterns instead of those of single nutrients or foods. The dietary model with the largest body of evidence of health benefit is that traditionally followed by inhabitants of some Mediterranean countries. There is evidence confirming the inverse association of adhering to Mediterranean diet with overweight and obesity. Four meta-analyses of randomized controlled trials, including up to 16 trials, have shown a greater reduction of body weight and BMI with MedDiet compared to other diets, while a meta-analysis of 7 prospective cohort studies, found a reduced risk of becoming obese and gaining weight over time associated with a higher adherence to MedDiet. This narrative review examines studies reporting inverse associations of a higher adherence to the MedDiet with overweight/obesity and with age-associated chronic diseases related to obesity.